Encapsulation of Dadih with Maltodextrin and Gum Arabic: Effect on Nutritional and Sensory Properties of Probiotic Instant Milk - Novelina; Syukri, Daimon; Mahfuzatul Khairani (Universitas Ahmad Dahlan, 2025)
The conversion of dadih, a traditional Indonesian fermented buffalo milk, into a probiotic instant milk powder can enhance its shelf life and commercial potential. This study aimed to evaluate the impact of encapsulating dadih using maltodextrin (MD) and gum Arabic (GA) on the physicochemical properties and sensory characteristics of the resulting probiotic instant milk. The dadih was encapsulated with varying MD and GA ratios (100%:0%, 80%:20%, 70%:30%, 60%:40%, 50%:50%) and processed using freeze drying. Moisture, ash, protein, fat content, and lactic acid bacteria (LAB) viability were analyzed. The results showed that higher gum Arabic content increased moisture and ash, while maltodextrin contributed to higher protein and fat retention. The highest LAB count was observed in the 100% MD formulation, indicating that maltodextrin was more effective in preserving probiotics. Sensory evaluation indicated that the 70% MD and 30% GA formulations provided the best texture and flavor making them the most preferred among consumers. This study concludes that the encapsulation ratio of MD and GA plays a crucial role in optimizing the physicochemical properties, probiotic survival, and sensory quality of the probiotic instant milk, offering valuable insights for improving product stability and consumer acceptance.